Karakteristik Sifat Fisik dan Kimia Edible Film Pati Sagu Rumbia (Metroxylon sagu Rottb) untuk Bahan Baku Cangkang Kapsul (Characteristics of Physical and Chemical Properties of Edible Film of Rumbia Sago Starch for Capsule Shell Material) - Hamlan Ihsan; Nadra Khairiah; Rufida Rufida (Jurnal Riset Industri Hasil Hutan, 2018)
The purpose of this research was to analyze the physical and chemical properties of sago starch edible film (Metroxylon sagu Rottb) as capsule shells material. The research was started with the extraction of the rumbia starch, and was followed with the production of edible film added with modified carrageenan concentrations (20% and 30% w/w) to the main compound. Organoleptic test showed that the color and odor of the films were normal. Water content of wet sago and dry sago was 12.55%, and 5.38%, respectively. Although the addition of carrageenan increased the water content but still corresponded with SNI gelatin quality standard with a maximum of water content of 16%. The ash content of fresh sago and dry sago was 0.36% and 1.09%, respectively, and the content increased significantly with the addition of carrageenan. The pH of all varied samples was 5.5 – 7.0, and the pH was in accordance with SNI. Meanwhile, the heavy metal content of the samples measured by means of AAS was negative. Based on viscosity testing withBrookfield method, high carrageenan concentration led to low viscosit. tensile strength test based on ASTM D 882-2002 gave positive results for dry sago (21.05 kg/cm2) whereas fresh sago with modified 20% and 30% carrageenan had tensile strength of 5.33 kg/cm2 and 18.18 kg/cm2, respectively. The results showed that sago starch had the potential as a raw material for producing soft capsules by modified composition to enhance physical and mechanical properties in order to meet the quality standard of edible film.